Defecation practices in residents of urban slums and rural areas of hubballi, Dharwad: a cross sectional study - Bathija, Geeta V.; Sarvar, Rana (International Journal Of Community Medicine And Public Health, 2017)
Background: The unsafe disposal of excreta is a principal cause in the transmission of pathogens within the environment and improvements in excreta management provide significant reductions in diarrhoeal diseases. Objectives of present study are to understand the factors impacting on defecation practices and to study the prevailing defecation practices in adults and children and to assess the knowledge and attitudes with regard to sanitation practices in rural areas and urban slums of Hubballi, Dharwad, Karnataka. Methods: A community based cross sectional study was conducted in 3 areas of Hubballi and Rural Areas of Noolvi. A total of 120 households were visited; 55 of urban and 65 rural. The adult member of the household was interviewed about the sanitary practices followed and their knowledge and attitude towards Safe Sanitation and Open Air Defecation was assessed. Results: 64.18% of the households had an independent toilet in their house (87% in urban and 44.6% in rural). Among these, in only 85% households the toilet was used by all members. While in 11 houses some individuals preferred open air defecation. The practice of open air defecation was found in 44.16% of study sample (21% in urban slums and 63% in rural areas). In children, usage of toilets was only 46.5%. 54% children practiced open air defecation (28.8% in urban slums, 80% in rural areas). The usual sites for open air defecation were open fields (77%), alongside gutter (3%) and streets (20%). Conclusions: According to World Health Organisation, open defecation is the “riskiest sanitation practice of all.” Effort from individuals, communities and government is essential to achieve the goal of open defection free India.